Pepsin-Digested Bovine Lactoferrin Induces Apoptotic Cell Death With JNK/SAPK Activation in Oral Cancer Cells - Takayuki Sakai; Yoshiko Banno; Yukihiro Kato; Yoshinori Nozawa; Mitsuru Kawaguchi (Elsevier, 2005)
Lactoferrin, a member of the transferrin family, is iron-binding and a strongly cationic 76 kDa glycoprotein. In breast milk it is secreted in high concentrations from glandular epithelia and is also present in other exocrine fluids including saliva. In the present study, we examined the biological mechanisms of apoptosis induced by pepsin-digested-lactoferrin peptide (Lfn-p) in the human oral squamous cell carcinoma cell line SAS. We found that treatment with Lfn-p induced cell death with apoptotic nuclear changes, preceded by the cleavage of caspase-3 and poly (ADP-ribose) polymerase (PARP) in the apoptotic cells. Treatment with Lfn-p induced phosphorylation of extracellular signal-regulated kinase (ERK1/2), a member of the MAP kinase family, at early stages of apoptosis. Another MAP kinase, c-Jun N-terminal kinase/stress-activated protein kinase (JNK/SAPK), was also phosphorylated by treatment with Lfn-p. Pretreatment of SAS cells with SP600125, a JNK/SAPK inhibitor, diminished Lfn-induced apoptosis, as assessed by determining released lactate dehydrogenase activity. On the other hand, the MEK1 inhibitors PD98059 or U0126 showed no effect on repression of cell death, but rather an increase. These results suggest that JNK/SAPK activation may play an important role in Lfn-p-induced apoptotic cell death of human oral squamous cell carcinoma cells. Keywords:: lactoferrin, apoptosis, oral cancer, extracellular signal-regulated kinase, c-Jun N-terminal kinase/stress-activated protein kinase